Prediction of Resthenosis After Carotid Endarterectomy by the Method of Computer Simulation - A. N. Kazantsev; R. A. Vinogradov; Yu. N. Zakharov; V. G. Borisov; M. A. Chernyavsky; V. N. Kravchuk; D. V. Shmatov; K. P. Chernykh; A. A. Sorokin; G. Sh. Baghdavadze; S. V. Artyukhov; G. G. Khubulava (Неотложная медицинская помощь)
The article describes a computer modeling technique that allows predicting the development of restenosis of the internal carotid artery after carotid endarterectomy (CEE). A clinical case has been demonstrated that proves the effectiveness of the developed method. It is indicated that for the correct formation of the geometric model, data from multispiral computed tomography with angiography of the patient after CEE with a layer thickness of 0.6 mm and a current of 355 mA are required. To build a flow model, data of color duplex scanning in three sections are required: 1. In the proximal section of the common carotid artery (3 cm proximal to the bifurcation); 2. In the section of the external carotid artery, 2 cm distal to the carotid sinus; 3. In the section of the internal carotid artery, 2 cm distal to the carotid sinus. The result of computer calculations using specialized software (Sim Vascular, Python, Open Foam) is a mathematical model of blood flow in a vessel. It is an array of calculated data describing the speed and other characteristics of the flow at each point of the artery. Based on the analysis of RRT and TAWSS indicators, a computer model of bifurcation is formed, which makes it possible to predict areas of increased risk of restenosis development. Thus, the developed technique is able to identify a cohort of patients after CEE, subjected to a high probability of loss of the vessel lumen. Such an opportunity will provide a more precise supervision of these patients in the postoperative period with the aim of early diagnosis of restenosis and timely prevention of the development of adverse cardiovascular events.